(3JGQjN GdeSYhOis - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bGd GdeSYhOi hbO bjd hLgg UGdM GdfHi Ydjg GdSdGe Ydi UObGJ aNGda CeQg hCSGA GdSjQI s
(3BNQgG (B:s
(3jfJgi CKfGA PcQ GdHjhJ GdeYXeI YfO GdUbGdHI s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B80s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs